Resting-State Alpha-Band Oscillations in Migraine. (April 2018) - O'Hare, Louise; Menchinelli, Federica; Durrant, Simon J.
Migraine groups show differences in motion perception compared with controls, when tested in between migraine attacks (interictally). This is thought to be due to an increased susceptibility to stimulus degradation (multiplicative internal noise). Fluctuations in alpha-band oscillations are thought to regulate visual perception, and so differences could provide a mechanism for the increased multiplicative noise seen in migraine. The aim of this article was to characterise resting-state alpha-band oscillations (between 8 and 12 Hz) in the visual areas of the brain in migraine and control groups. Alpha-band activity in the resting state (with eyes closed) was recorded before and after a visual psychophysics task to estimate equivalent noise, specifically a contrast detection task. The lower alpha-band (8 to 10 Hz) resting-state alpha-band power was increased in the migraine compared with the control group, which may provide a mechanism for increased multiplicative noise. In agreement with previous research, there were no differences found in the additive (baseline) internal noise, estimated using an equivalent noise task in the same observers. As fluctuations in alpha-band oscillations control the timing of perceptual processing, increased lower alpha-band (8 to 10 Hz) power could explain the behavioural differences in migraine compared with control groups, particularly on tasks relying on temporal integration.